Perlindungan Hukum Terhadap Lingkungan Hidup untuk Mengurangi Illegal Loging di Kota Medan - Lubis, Muhammad Ridwan; Harahap, Herlina Hanum; Gultom, Juanda (Universitas Islam Sumatera Utara, 2024)
Data released by the World Bank shows that from 1985-1997 Indonesia has lost about 1.5 million hectares of forest each year and it is estimated that about 20 million production forests remain. Illegal logging is related to the increasing demand for timber in the international market, the large installed capacity of the domestic timber industry, local consumption, weak law enforcement, and timber bleaching that occurs outside the logging area. Based on the results of the FWI and GFW analysis over a period of 50 years, Indonesia's forest cover has decreased by around 40% of the total forest cover throughout Indonesia. And mostly, forest destruction (deforestation) in Indonesia is the result of a political and economic system that considers forest resources as a source of income and can be exploited for political interests and personal gain. The problem is with how Legal Protection of the environment to reduce Illegal Logging in Medan City. The method used is empirical juridical research method, which is a legal research conducted by examining directly and coupled with reviewing the literature to obtain further explanation. In terms of sociological legal research using laws and regulations related to the title. The result of the research is that it must play a more active role in protecting the environment so that plants in the city of Medan are well maintained. Keywords: Protection, Environment, and Illegal Logging